Clinical Efficacy and Safety of Proton and Carbon Ion Radiotherapy for Prostate Cancer: A Systematic Review and Meta-Analysis - Li, Meixuan; Li, Xiuxia; Yao, Liang; Han, Xue; Yan, Wenlong; Liu, Yujun; Fu, Yiwen; Wang, Yakun; Huang, Min; Zhang, Qiuning; Wang, Xiaohu; Yang, Kehu (Frontiers in Oncology, 2021)
Background: Carbon ion radiotherapy (CIRT) and proton beam therapy (PBT) are promising methods for prostate cancer, however, the consensus of an increasing number of studies has not been reached. We aimed to provide systematic evidence for evaluating the efficacy and safety of CIRT and PBT for prostate cancer by comparing photon radiotherapy. Materials and Methods: We searched for studies focusing on CIRT and PBT for prostate cancer in four online databases until July 2021. Two independent reviewers assessed the quality of included studies and used the GRADE approach to rate the quality of evidence. R 4.0.2 software was used to conduct the meta-analysis. A meta-regression test was performed based on the study design and tumor stage of each study. Results: A total of 33 studies including 13 CIRT and 20 PBT-related publications, involving 54101 participants were included. The quality of the included studies was found to be either low or moderate quality. Random model single-arm meta-analysis showed that both the CIRT and PBT have favorable efficacy and safety, with similar 5-year overall survival (OS) (94% vs 92%), the incidence of grade 2 or greater acute genitourinary (AGU) toxicity (5% vs 13%), late genitourinary (LGU) toxicity (4% vs 5%), acute gastrointestinal (AGI) toxicity (1% vs 1%), and late gastrointestinal (LGI) toxicity (2% vs 4%). However, compared with CIRT and PBT, photon radiotherapy was associated with lower 5-year OS (72%-73%) and a higher incidence of grade 2 or greater AGU (28%-29%), LGU (13%-14%), AGI (14%-19%), and LGI toxicity (8%-10%). GRADE assessment results indicated that the certainty of the evidence was very low. Meta-regression results did not show a significant relationship based on the variables studied (P<0.05). Conclusions: Currently available evidence demonstrated that the efficacy and safety of CIRT and PBT for prostate cancer were similar, and they may significantly improve the OS, LCR, and reduce the incidence of GU and GI toxicity compared with photon radiotherapy. However, the quantity and quality of the available evidence are insufficient, more high-quality controlled studies are needed in the future.